THE EFFECT OF PROVIDING POSTER MEDIA EDUCATION ABOUT HYPERTENSION ON KNOWLEDGE CONTRACTOR WORKERS IN THE EAST TELUKJAMBE COMMUNITY HEALTH CENTER WORK AREA - Hegar Nur Rosmalati, Putri; Sefrina, Linda Riski (HEARTY, 2024)
Hypertension is a serious health problem that can affect the productivity and welfare of workers in various sectors, including the construction industry. Hypertension experienced by construction workers is caused by smoking habits, excessive coffee consumption and a family history of hypertension. This study aims to determine the effect of poster media education about hypertension on the knowledge of contractor workers in the East Telukjambe Health Center work area. This research uses quantitative methods in the form of analytical research with a cross-sectional study design with a sample size of 30 people using random sampling techniques. Hypertension data collection uses a blood pressure monitor and data collection instruments for age, weight, height, income, blood pressure, smoking habits, coffee consumption. As a result of the research, it can be concluded that there is a relationship between the influence of providing educational media about hypertension on the knowledge of contractor workers in the East Telukjambe Community Health Center work area as evidenced by the results of statistical tests using the chi square test, which shows a p-value of 0.00 < 0.05, which means there is an influence between providing education using posters with knowledge related to hypertension.